Effectiveness and Safety of Oxcarbazepine vs. Levetiracetam as Monotherapy for Infantile Focal Epilepsy: A Longitudinal Cohort Study - Zhao, Binyang; Liao, Shuang; Zhong, Xuefei; Luo, Yuanyuan; Hong, Siqi; Cheng, Min; Zhang, Jie; Li, Tingsong; Jiang, Li (Frontiers in Neurology, 2022)
Objective: To compare the effectiveness and safety of oxcarbazepine (OXC) versus levetiracetam (LEV) for treating infantile focal epilepsy in a longitudinal cohort study. Methods: We enrolled 187 consecutive patients aged 2–24 months who received OXC or LEV as initial monotherapy; 161 patients completed the study. The longitudinal analysis involved anti-seizure medication (ASM) responsiveness, safety, establishment of epilepsy syndrome, and etiology over a median follow-up of 2.0 years (interquartile range [IQR] 1.6–2.4). The relative efficacy and retention rates of OXC versus LEV were evaluated using generalized linear regression models and the Cox proportional hazards model. Results: The 161 patients who completed the study had comparable baseline demographics and clinical variables between the OXC group (n = 83) and LEV group (n = 78). Overall, the mean age at onset was 6.0 months (IQR 4.3–9.0). The most common epilepsy syndrome was self-limited familial/non-familial infantile epilepsy (54.7%). Epilepsy was related to genetic and unknown causes in 34.2% and 52.2% of the patients, respectively. OXC achieved significantly higher responses than LEV for seizure freedom (risk ratio [RR] = 1.71, 95% confidence interval [CI] = 1.28–2.73, P < 0.001) and 12-month retention rate after onset (hazard ratio [HR] = 1.84, 95% CI = 1.15–2.95, P = 0.007). Moreover, OXC showed more obvious effects for patients aged <1 year diagnosed with self-limited familial/non-familial infantile epilepsy and non-syndromic epilepsy with genetic or unknown causes. The adverse events related to both OXC and LEV were well-tolerated. Significance: OXC could be an alternative to LEV for treating infantile focal epilepsy. OXC monotherapy can be considered first-line treatment for patients aged <12 months and those with epilepsy without developmental and epileptic encephalopathy.